2017
DOI: 10.1093/jac/dkx471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenem resistance and carbapenemase production among Enterobacteriaceae isolated from urine in the UK: results of the UK infection-Carbapenem Resistance Evaluation Surveillance Trial (iCREST-UK)

Abstract: The frequency of confirmed CPE among Gram-negative urinary isolates was low, at 0.13% (10/7504), but CPE were found in urines at all five participating sites and the diversity of carbapenemase genes detected reflected the complex epidemiology of CPE in the UK. These data can inform local policies about the cost-effectiveness and clinical value of testing Gram-negative bacteria from urine specimens routinely against a carbapenem as part of patient management and/or infection prevention and control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In Wales, IMP, NDM, VIM, KPC and OXA-48-like (known as the "big five") are the carbapenemases predominantly identified and consistent with those found in the rest of the UK: in particular, IMP, NDM, KPC and OXA-48-like in Enterobacteriales [2] and VIM in Pseudomonas species [3]. Phenotypic assays employing inhibitors for the different enzymes are available for the detection of some carbapenemases.…”
Section: Introductionmentioning
confidence: 58%
“…In Wales, IMP, NDM, VIM, KPC and OXA-48-like (known as the "big five") are the carbapenemases predominantly identified and consistent with those found in the rest of the UK: in particular, IMP, NDM, KPC and OXA-48-like in Enterobacteriales [2] and VIM in Pseudomonas species [3]. Phenotypic assays employing inhibitors for the different enzymes are available for the detection of some carbapenemases.…”
Section: Introductionmentioning
confidence: 58%
“…Data regarding important CRE studies in Taiwan and other countries are shown in Table 1 . There were big variations in the rates of CPE among clinical CRE isolates in Taiwan as compared to those from other countries ( Lorenzoni et al, 2017 ; Woodford et al, 2017 ; Laolerd et al, 2018 ). It is notable that persistently high KPC-2 rates (73.9% in 2012, and 61.1% in 2015) and emergence of KPC-17 as well as KPC-34 since 2014 were observed ( Chiu et al, 2018 ).…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 88%
“…Especially OXA-48-like enzymes are weak carbapenemases and the strains having bla OXA-48-like genes can have very low carbapenem MICs. However, also these kinds of strains seem to be very rare [8,19,20].…”
Section: Discussionmentioning
confidence: 99%